2023
DOI: 10.1002/anie.202218321
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ion Transport in Two‐Dimensional Lamellar Nanochannel Membranes

Abstract: Precise and ultrafast ion sieving is highly desirable for many applications in environment-, energy-, and resource-related fields. The development of a permselective lamellar membrane constructed from parallel stacked twodimensional (2D) nanosheets opened a new avenue for the development of next-generation separation technology because of the unprecedented diversity of the designable interior nanochannels. In this Review, we first discuss the construction of homo-and heterolaminar nanoarchitectures from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 226 publications
(431 reference statements)
2
20
0
Order By: Relevance
“…We also investigated the impacts of salt concentration and membrane composition on ion sieving. Prior research has often shown reduced cation or anion selectivity as a result of the diminished range of the surface charge under high-concentration conditions, according to the Poisson–Boltzmann theory. ,, However, we confirmed relatively stable ion sieving performance when the chloride salt concentration was varied between 0.05 and 0.2 M, as illustrated in Figure d. This indicated that selective ion transport based on specific binding interactions with the crown ether molecules was not significantly affected by the ion concentration.…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…We also investigated the impacts of salt concentration and membrane composition on ion sieving. Prior research has often shown reduced cation or anion selectivity as a result of the diminished range of the surface charge under high-concentration conditions, according to the Poisson–Boltzmann theory. ,, However, we confirmed relatively stable ion sieving performance when the chloride salt concentration was varied between 0.05 and 0.2 M, as illustrated in Figure d. This indicated that selective ion transport based on specific binding interactions with the crown ether molecules was not significantly affected by the ion concentration.…”
Section: Resultssupporting
confidence: 69%
“…SEM observations of the CTM surface morphology (Figures a and S3) showed an intact membrane surface without structural defects such as cracks and holes. However, as with other 2D lamellar membranes, a typical wrinkled morphology was formed due to irregular stacking during the preparation process . Moreover, SEM observations of the cross-section (Figure b,c) clearly showed a layered structure, indicating that the Ti 3 C 2 T x nanosheet skeleton was not destroyed by the introduction of crown ether rings.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations